2012
DOI: 10.1002/jsfa.5851
|View full text |Cite
|
Sign up to set email alerts
|

Time of methyl jasmonate application influences the development of ‘Cripps Pink’ apple fruit colour

Abstract: A single pre-harvest spray of MJ (10 mmol L(-1)) at 169 DAFB or MJ (5 mmol L(-1)) at 186 DAFB was effective in improving the red blush and export grade fruit through accumulation of flavonoids in fruit skin without adversely affecting quality at harvest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
2
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 47 publications
4
29
2
3
Order By: Relevance
“…Bizjak et al (2013) reported that L* values decreased during advanced maturity in Braeburn apples, indicating darker fruit peels. Decreasing L* values were also reported with postharvest MeJA treatments in Golden Delicious and Fuji apples (Fan et al, 1998;Fan and Mattheis, 1999) and with preharvest treatments in Cripps Pink apples (Shafiq et al, 2013). Similarly in the present study, parameter L* decreased linearly with MeJA treatments regardless of the application regime.…”
Section: Discussionsupporting
confidence: 87%
“…Bizjak et al (2013) reported that L* values decreased during advanced maturity in Braeburn apples, indicating darker fruit peels. Decreasing L* values were also reported with postharvest MeJA treatments in Golden Delicious and Fuji apples (Fan et al, 1998;Fan and Mattheis, 1999) and with preharvest treatments in Cripps Pink apples (Shafiq et al, 2013). Similarly in the present study, parameter L* decreased linearly with MeJA treatments regardless of the application regime.…”
Section: Discussionsupporting
confidence: 87%
“…Increasing MeJA treatments linearly increased the total phenolics contents of apples (Table 2). Shafiq et al [26] also reported increased flavonoid levels Downloaded by [Selcuk Universitesi] at 10:58 07 February 2015 with pre-harvest MeJA treatments in "Cripps Pink" apples. Similarly, pre-harvest MeJA treatments increased the flavonoid levels in blueberries, [27] blackberries, [28] and grapes.…”
Section: Resultsmentioning
confidence: 96%
“…These characteristics vary based on growth period, soil and ecological conditions, plant nutrients, type of production (organic or inorganic), harvest time and other cultural practices (Meashami, 2011). Other researchers (Zhang and Whiting, 2011;Shafiq et al, 2013) reported direct impacts in growth regulators on physical, mechanical and biochemical properties of the fruits.…”
Section: Introductionmentioning
confidence: 95%
“…Sweet cherry is a non-climacteric fruit and therefore rapidly losses peel color and flesh firmness because of higher post-harvest respiration rates. Despite some contrary opinions (Remon et al, 2003), various researchers (Estia et al, 2002;Shafiq et al, 2013) reported that such losses in peel color and flesh firmness were related to phenolics, antioxidants, anthocyanins and pectins in fruits (Crisosto et al, 2001). These characteristics vary based on growth period, soil and ecological conditions, plant nutrients, type of production (organic or inorganic), harvest time and other cultural practices (Meashami, 2011).…”
Section: Introductionmentioning
confidence: 99%